Esthetic outcome of immediately placed and nonfunctionally loaded implants in the anterior maxilla utilizing a definitive abutment: A pilot clinical trial - AlTarawneh, Sandra (Dent Res J (Isfahan), 2020)
BACKGROUND: Immediate dental implants placement and loading utilizing definitive abutments might save time and cost when an esthetic final result is anticipated. The objective of this prospective clinical trial was to evaluate the esthetic outcome of immediate implantation and immediate nonfunctional loading utilizing definitive abutments, with and without bony substitutes filling the peri-implant gap. MATERIALS AND METHODS: In this clinical trial study a total of 11 implants were placed utilizing a flapless immediate post extraction approach in the maxilla (second premolar to second premolar). Atraumatic extraction was performed and implants were immediately placed. The gap was either left without grafting or filled with particulate bone material. Immediate nonfunctional loading was performed utilizing a definitive abutment. The pink esthetic scores (PESs) were assessed preoperatively, at 1- and 2-year follow-up periods. Dental casts were obtained at respective time intervals; scanned, registered, and closest point distances were measured. For all statistical tests, value of P = 0.05 was set as a statistical significance level. RESULTS: The mean of PES at baseline was 9.4 ± 1.69, at 1 year was 9.5 ± 2.07, at 2 years was 10.2 ± 2.75, for the graft group 10.3 ± 2.8, and for nongrafting group was 10.2 ± 2.59. There were no statistically significant differences in PESs at baseline when compared to 1- and 2-year intervals, and for grafting group versus nongrafting group (P = 0.24). Distances between the two time points for all cases were <1 mm in all reference planes. CONCLUSION: Immediate placement and nonfunctional loading utilizing a definitive abutment appear to result in a stable result as far as esthetic outcome and alveolar process sufficiency are concerned.